(untitled) (Research, Society and Development, 2020)
Minerals and vitamins are essential for the body’s functioning, and the missing of these micronutrients can cause dysfunctions in the body. The technology is undergoing great changes and always innovating, allowing patients to receive assistance through telemedicine, increasing the oferts. This study aims to relate the signs and symptoms of vitamin and mineral deficiency using technology to help prevent health. A data survey was carried out in PubMed, Scielo and Academic Google from the last two years and in a timeless manner. The selection of articles was based on the relevance data with 19 articles of vitamins, 13 of minerals and 3 of telemedicine being selected. Through research, the study covers all micronutrients with the respective signs and symptoms of their deficiency of water-soluble and fat-soluble vitamins and minerals chosen, in addition to identifying the foods that are sources of each micronutrient addressed in this paper. Telemedicine is an area that uses advanced interactive electronic and telecommunication technology to develop new responses that increase health competence, so telemedicine could assist in the detection of vitamin and mineral deficiencies through remote consultation.